Perencanaan Strategis Perpustakaan: Telaah Dokumen Renstra Perpustakaan Universitas Gadjah Mada - Bima Bijak Prasetyo; Laksmi Laksmi (Pustakaloka, 2021)
Strategic planning based on a visionary view is expected to avoid the uncertainty of steps taken in dealing with changes that occur in the future. UGM Library, in facing the changes that may occur in the future, also makes a strategic plan which is contained in a document that can be accessed by the public. This paper will attempt to dissect the Gadjah Mada University Library Strategic Plan 2017-2020 document. UGM Library by making the UGM Library Strategic Plan 2017-2020 in supporting the parent institution to carry out the tridarma of higher education and in achieving its vision and mission. Lack of macro analysis by considering political, economic, social and technological aspects, becomes an evaluation and recommendation for strategic planning in the next period.